Leg Muscle Strength and Balance in Edging Techniques in Jakarta's Rock-Climbing Athletes - Annisah Nur Aliyah; Hartman Nugraha; Hidayat Humaid (Musamus Journal of Physical Education and Sport (MJPES), 2024)
Objective. This study aims to investigate the correlation between leg muscle strength and edging technique better to understand the impact of strength training on skiing performance. Additionally, we aim to explore the relationship between balance and edging techniques and the interplay between leg muscle strength and balance in the context of edging technique. By examining these factors, we hope to gain valuable insights into how skiers can optimize their technique and improve their overall performance on the slopes. Material and Method. On December 13, 2023, a research data collection was conducted at the Jakarta International Wall Climbing. An associative quantitative research method with correlation studies was used in this research. The main goal of this study was to find out the correlation between variables. The population of this research was comprised of training athletes from Jakarta who were involved in rock climbing, and a sample of 30 individuals was selected through purposive sampling technique. The leg dynamometer was used for testing the leg muscle strength, while the one-stand balance test was used to evaluate the edging technique with the edging climbing test. Result. The data analysis results indicate that there is a direct and positive correlation between leg muscle strength (X1) and the efficiency of the edging technique (Y). This correlation is illustrated by the regression equation Ŷ = 1.272 + 0.063X₁, with a corresponding correlation coefficient (ryx1) value of 0.727. Similarly, the analysis also shows a positive correlation between balance (X2) and the effectiveness of the edging technique (Y), which is demonstrated by the regression equation Ŷ = 0.917 + 0.111X2, with a correlation coefficient (ryx2) value of 0.736. Furthermore, the study reveals that there is a positive correlation between running speed (X1) and balance (X2) with the results of the edging technique (Y), as indicated by the equation Ŷ = 0.692 + 0.035X1 + 0.66X2. The corresponding Ry1-2 correlation coefficient is 0.788. Conclusion. Rock climbing is a physically challenging sport that requires a great deal of strength and skill. One of the key aspects of climbing is having strong leg muscles, as this allows climbers to transfer maximum strength to their feet and maintain a sturdy grip on the footholds. With strong legs, climbers can put less pressure on their hands and rely more on their feet for support, making it easier to balance and climb effectively. To achieve this optimal level of strength and control, it's essential to engage in regular leg strength training exercises that focus on building up the muscles used in edging. By doing so, climbers can improve their abilities and tackle even more difficult routes with confidence and ease.